Public perceptions of diabetes, healthy living, and conversational agents in Singapore: needs assessment - Dhinagaran, Dhakshenya Ardhithy (2022)
The incidence of chronic diseases such as type 2 diabetes is increasing in countries worldwide, including Singapore. Health professional-delivered healthy lifestyle interventions have been shown to prevent type 2 diabetes. However, ongoing personalized guidance from health professionals is not feasible or affordable at the population level. Novel digital interventions delivered using mobile technology, such as conversational agents, are a potential alternative for the delivery of healthy lifestyle change behavioral interventions to the public.